Optimizing the Utilization of Sawdust Waste in Mantingan Village, Jepara Regency - Prianka Ratri Nastiti; Efriyani Sumastuti (Jurnal Pengabdian Pancasila (JPP), 2023)
The waste of sawdust left over from furniture crafts in Mantingan Village, Jepara is one of the main problems for the village. This Community Service Program was carried out to optimize the potential of sawdust waste in Mantingan Village. The results show that with training on making crafts using sawdust waste, digital marketing training with Shopee, product packaging and labeling, as well as socialization regarding product protection can help the people of Mantingan Village to overcome the problem of sawdust waste so that it has the potential to improve the economy of the surrounding community by selling handicrafts from sawdust waste through online sales.